Structural method for determining deformations by geodetic measurements - Gladilin, Valeriy; Belenok, Vadim; Hebryn-Baidy, Liliia; Chookarina, Natali (Geodesy and Cartography, 2019)
Industrial equipment is a dynamic system that deforms during installation (assembly) and during operation. Under the influence of variable load and mixing of the center of gravity of the equipment and foundations on which it is installed, uneven horizontal and vertical displacements occur, therefore individual equipment elements are unevenly deformed, which can lead to poor performance or stoppage of this equipment. Timely measurement of the displacement of certain points of equipment (deformations) of precision equipment with the help of geodetic and other methods and their correct use for correcting the geometry of the equipment will contribute to improving the operational properties and increasing the period of uninterrupted operation of equipment’s, for example, precision conveyor lines for assembling cars.